Development and validation of a standard area diagram set for assessment of anthracnose severity on cucumber leaves - Conforto, Erica Cinthia; Brainer Martins, Ricardo; Nicoli, Alessandro; Capucho, Alexandre Sandri; Duarte, Henrique da Silva Silveira; Michereff, Sami Jorge (Wiley, 2024)
Anthracnose, caused by species in the Colletotrichum orbiculare complex, is a major foliar disease in open-field cucumber farming worldwide. This study aimed to develop and validate a standard area diagram (SAD) set to estimate the severity of anthracnose on cucumber leaves. For this purpose, a SAD set with nine levels of severity (1; 3; 5; 10; 20; 30; 40; 50 and 60%) is proposed. The SAD set was validated by 16 raters with no experience in evaluating plant diseases. Both accuracy and precision improved when the proposed SAD set was employed. The statistical parameters were bias coefficient factor-Cb (no SAD set = 0.891, with SAD set = 0.982); correlation coefficient- r (no SAD set = 0.851, with SAD set = 0.941); and Lin's concordance correlation coefficient-ρc (no SAD set = 0.755, with SAD set = 0.924). In addition, estimates were more reliable: intra-class correlation coefficient-ρ (no SAD set = 0.646, with SAD set = 0.887). The SAD set proposed here is a useful tool for improving visual assessments of anthracnose severity on cucumber leaves.